The Race Between Education, Technology, and the Minimum Wage - Jonathan Vogel (The Quarterly Journal of Economics, 2025)
ABSTRACT What is the effect of the real minimum wage on wages and inequality? I develop a theory that nests the race between education and technology. The theory predicts that the effect of changes in minimum wages is initially small but grows over time. I present empirical evidence of these dynamic effects: the elasticity of real wages grows substantially over a three-year period. I show that minimum wages help rationalize a considerable decline in real wages of low-education workers in the 1980s and play a role in shaping the evolution of the U.S. college premium.